2014
DOI: 10.1128/jb.01687-14
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Commitment, Blocking, and Continuation of Nutrient Germination of Individual Bacillus subtilis Spores

Abstract: bShort exposures of Bacillus spores to nutrient germinants can commit spores to germinate when germinants are removed or their binding to the spores' nutrient germinant receptors (GRs) is inhibited. Bacillus subtilis spores were exposed to germinants for various periods, followed by germinant removal to prevent further commitment. Release of spore dipicolinic acid (DPA) was then measured by differential interference contrast microscopy to monitor germination of multiple individual spores, and spores did not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
2
14
1
Order By: Relevance
“…Under laboratory conditions, spores of B. subtilis are often heat activated (HA) for 30 min at 70°C to increase their germination responses to nutrients (51)(52)(53). In this study, germination (which, under a phase-contrast microscope, is reflected by the phase-bright to phase-dark transition of spores) in response to L-alanine and AGFK was assessed for HA and non-HA spores of various B. subtilis strains that exhibit low to extremely high heat resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Under laboratory conditions, spores of B. subtilis are often heat activated (HA) for 30 min at 70°C to increase their germination responses to nutrients (51)(52)(53). In this study, germination (which, under a phase-contrast microscope, is reflected by the phase-bright to phase-dark transition of spores) in response to L-alanine and AGFK was assessed for HA and non-HA spores of various B. subtilis strains that exhibit low to extremely high heat resistance.…”
Section: Resultsmentioning
confidence: 99%
“…In most experiments, germination of multiple individual spores was monitored by PC microscopy as described previously (11,(20)(21)(22). Changes in wild-type spores' PC image intensities at least through T release of germination are almost certainly due to changes in spores' CaDPA content, and this is also true for analyses of spore germination by DIC microscopy (see below) (9)(10)(11).…”
Section: Methodsmentioning
confidence: 99%
“…In experiments measuring spores' commitment to germinate, spores were germinated with 10 mM L-valine for 10 min at various temperatures, and then the L-valine was replaced with 10 mM D-alanine in 25 mM K-HEPES buffer (pH 7.4) as described previously (20) and incubation was continued at 37°C. Previous work has shown that D-alanine addition to spores germinating with L-valine blocks further commitment but allows completion of the germination of spores that had become committed prior to D-alanine addition (7).…”
Section: Methodsmentioning
confidence: 99%
“…Successive stages of the germination and outgrowth of bacterial spores, observed under phase-contrast microscopy and methods applied for monitoring. Commitment to germination can be followed by the release of CaDPA (Zhang, Liang, Yi, Setlow, & Li, 2014). Spores remain phase-bright.…”
Section: Culture Dependent Methods and Indirect Measurements (Fig 2aeb)mentioning
confidence: 99%
“…Spore germination can be monitored by titration in the culture medium of CaDPA released by spores (5. Zhang et al, 2014). Bioluminescence methods consist in observing bioluminescence of lux-containing engineered spores (6.…”
Section: Microscopy and Flow Cytometry Methods (Fig 2ced)mentioning
confidence: 99%